Question
upstudy study bank question image url

Latihan Gunakan metode pecahan parsial untuk menentukan integral-integral berikut \( 0 \int \frac{x^{3}}{x-5} d x \) \( 0 \int \frac{7 x-7}{x^{2}-5 x-6} d x \) \( \int \frac{3}{(x+1)\left(x^{2}-x\right)} d x \)

Ask by Rodriguez Stephens. in Indonesia
Feb 13,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

1. ∫ x³⁄(x – 5) dx = (x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C 2. ∫ (7x – 7)/(x² – 5x – 6) dx = 5 ln|x – 6| + 2 ln|x + 1| + C 3. ∫ 3⁄[(x + 1)(x² – x)] dx = –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C

Solution

We will evaluate the following integrals using the method of partial fractions: 1) ∫ x³⁄(x – 5) dx 2) ∫ (7x – 7)/(x² – 5x – 6) dx 3) ∫ 3⁄[(x + 1)(x² – x)] dx Below are the step‐by‐step solutions. ──────────────────────────── 1) ∫ x³⁄(x – 5) dx Step 1. Since the degree of the numerator (3) is greater than that of the denominator (1), we start with polynomial division. Divide x³ by (x – 5): • Divide: x³ ÷ x = x²   Multiply back: x² · (x – 5) = x³ – 5x² • Subtract:   x³ – (x³ – 5x²) = 5x² • Bring down the “0x” (if you wish to keep the process formal) and continue:   Divide: 5x² ÷ x = 5x   Multiply back: 5x · (x – 5) = 5x² – 25x • Subtract:   5x² – (5x² – 25x) = 25x • Next, divide: 25x ÷ x = 25   Multiply back: 25 · (x – 5) = 25x – 125 • Subtract:   25x – (25x – 125) = 125 Thus, we have:   x³⁄(x – 5) = x² + 5x + 25 + 125⁄(x – 5). Step 2. Now integrate term‐by‐term:   ∫ x³⁄(x – 5) dx = ∫ (x² + 5x + 25) dx + 125 ∫ 1⁄(x – 5) dx Compute the integrals:   ∫ x² dx = (x³)/3   ∫ 5x dx = (5x²)/2   ∫ 25 dx = 25x   ∫ 1⁄(x – 5) dx = ln|x – 5| Thus the answer is:   (x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C ──────────────────────────── 2) ∫ (7x – 7)/(x² – 5x – 6) dx Step 1. Factor the denominator. Notice:   x² – 5x – 6 = (x – 6)(x + 1). Step 2. Write the integrand in partial fractions:   (7x – 7)/[(x – 6)(x + 1)] = A⁄(x – 6) + B⁄(x + 1). Multiply both sides by (x – 6)(x + 1):   7x – 7 = A(x + 1) + B(x – 6). Step 3. Solve for A and B. Expand the right-hand side:   A(x + 1) + B(x – 6) = (A + B)x + (A – 6B). Equate coefficients with 7x – 7:   Coefficient of x: A + B = 7   Constant term: A – 6B = –7 Solve:   From A + B = 7, we get A = 7 – B.   Substitute into A – 6B = –7:    (7 – B) – 6B = –7 ⟹ 7 – 7B = –7 ⟹ –7B = –14 ⟹ B = 2.   Then A = 7 – 2 = 5. Step 4. Write and integrate:   ∫ (7x – 7)/(x² – 5x – 6) dx = 5 ∫ 1⁄(x – 6) dx + 2 ∫ 1⁄(x + 1) dx     = 5 ln|x – 6| + 2 ln|x + 1| + C ──────────────────────────── 3) ∫ 3⁄[(x + 1)(x² – x)] dx Step 1. Factor the quadratic part:   x² – x = x(x – 1). Thus, the denominator becomes:   (x + 1)x(x – 1). Step 2. Write the partial fractions decomposition:   3⁄[x(x – 1)(x + 1)] = A⁄x + B⁄(x – 1) + C⁄(x + 1). Multiply through by x(x – 1)(x + 1):   3 = A (x – 1)(x + 1) + B x(x + 1) + C x(x – 1). Simplify each term:   A (x – 1)(x + 1) = A (x² – 1)   B x(x + 1) = B (x² + x)   C x(x – 1) = C (x² – x). Combine like terms:   3 = (A + B + C)x² + (B – C)x – A. Step 3. Equate coefficients with the constant 3 (which is 0·x² + 0·x + 3):   Coefficient of x²: A + B + C = 0   Coefficient of x:  B – C = 0   Constant term: –A = 3 ⟹ A = –3 From B – C = 0, we have B = C. Then from A + B + C = 0:   –3 + 2B = 0 ⟹ 2B = 3 ⟹ B = 3⁄2, and C = 3⁄2. Step 4. Write the decomposition and integrate:   3⁄[x(x – 1)(x + 1)] = –3⁄x + (3⁄2)⁄(x – 1) + (3⁄2)⁄(x + 1). Thus, the integral becomes:   ∫ 3⁄[(x + 1)(x² – x)] dx = –3 ∫ 1⁄x dx + (3⁄2) ∫ 1⁄(x – 1) dx + (3⁄2) ∫ 1⁄(x + 1) dx     = –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C ──────────────────────────── Final Answers: 1) ∫ x³⁄(x – 5) dx = (x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C 2) ∫ (7x – 7)/(x² – 5x – 6) dx = 5 ln|x – 6| + 2 ln|x + 1| + C 3) ∫ 3⁄[(x + 1)(x² – x)] dx = –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C These are the integrals evaluated using the method of partial fractions.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

Mari kita mulai dengan menyelesaikan integral-integral yang diberikan menggunakan metode pecahan parsial! Untuk integral pertama \( \int \frac{x^{3}}{x-5} d x \), kita akan membagi \( x^3 \) dengan \( x-5 \). Melakukan pembagian polinomial, kita mendapatkan: \[ x^3 \div (x-5) = x^2 + 5x + 25 + \frac{125}{x-5} \] Sehingga, integralnya menjadi: \[ \int x^2 + 5x + 25 + \frac{125}{x-5} \, dx = \frac{x^3}{3} + \frac{5x^2}{2} + 25x + 125 \ln|x-5| + C \] Selanjutnya, untuk integral kedua \( \int \frac{7 x-7}{x^{2}-5 x-6} d x \), kita harus memfaktorkan penyebutnya: \[ x^2 - 5x - 6 = (x-6)(x+1) \] Kemudian, kita terapkan pecahan parsial: \[ \frac{7x-7}{(x-6)(x+1)} = \frac{A}{x-6} + \frac{B}{x+1} \] Dengan menyamakan pecahan, kita temukan \( A \) dan \( B \): Setelah perhitungan, kita dapatkan \( A= 2 \) dan \( B = 5 \). Maka: \[ \int \frac{7x-7}{(x-6)(x+1)} \, dx = \int \left(\frac{2}{x-6} + \frac{5}{x+1}\right) \, dx = 2 \ln|x-6| + 5 \ln|x+1| + C \] Terakhir, untuk integral ketiga \( \int \frac{3}{(x+1)(x^2-x)} d x \), kita misalkan penyebutnya lebih besar dan menggunakan metode pecahan parsial: \[ \frac{3}{(x+1)(x^2-x)} = \frac{A}{x+1} + \frac{Bx + C}{x(x-1)} \] Silakan menghitung nilai \( A, B, \) dan \( C \) dengan menyamakan koefisien. Setelah itu, selesaikan integrasinya. Semoga penjelasan ini membantu dan menyenangkan! Selamat belajar!

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy